Mediterranean diet pattern and sleep duration and insomnia symptoms in the Multi-Ethnic Study of Atherosclerosis - Castro-Diehl, Cecilia; Wood, Alexis C; Redline, Susan; Reid, Michelle; Johnson, Dayna A; Maras, Janice E; Jacobs, David R; Shea, Steven; Crawford, Allison; St-Onge, Marie-Pierre (Sleep (New York, N.Y.), 2018)
Sleep duration and sleep quality are important predictors of risk for cardiovascular disease (CVD). One potential link between sleep health and CVD is through lifestyle factors such as diet. To clarify the association between diet and sleep, we assessed the associations of sleep duration and insomnia symptoms with current Mediterranean-style diet (aMed) and with historical changes in aMed score. Actigraphy-measured sleep duration and self-reported insomnia symptoms categorized as insomnia with short sleep (<6 hr/night), insomnia without short sleep, no insomnia with short sleep, and no insomnia or short sleep were obtained from 2068 individuals who also had dietary intake data. A 10-point aMed score, derived from a self-report food frequency questionnaire, was collected concurrently with the sleep assessment and 10 years before. Compared with individuals who currently reported a low aMed score, those with a moderate-high aMed score were more likely to sleep 6-7 vs. <6 hr/night (p < 0.01) and less likely to report insomnia symptoms occurring with short sleep (vs. no insomnia or short sleep alone; p < 0.05). An increase in aMed score over the preceding 10 years was not associated with sleep duration or insomnia symptoms. However, compared with those with decreasing aMed score, individuals with an unchanging score reported fewer insomnia symptoms (p ≤ 0.01). These results suggest that a Mediterranean-style diet is associated with adequate sleep duration, less insomnia symptoms, and less likely to have insomnia accompanied by short sleep. Further research should identify possible mediators through which diet may promote adequate sleep duration and reduce the risk of insomnia.